Coupling heterostructure of thickness-controlled nickel oxide nanosheets layer and titanium dioxide nanorod arrays via immersion route for self-powered solid-state ultraviolet photosensor applications. (January 2020) - Yusoff, M.M.; Mamat, M.H.; Abdullah, M.A.R.; Ismail, A.S.; Malek, M.F.; Zoolfakar, A.S.; Al Junid, S.A.M.; Suriani, A.B.; Mohamed, A.; Ahmad, M.K.; Shameem Banu, I.B.; Rusop, M.
Highlights: NiO nanosheets (NNS)/TiO2 nanorod arrays (TNAs) heterostructure were fabricated. A self-powered solid state UV photosensor was constructed using NNS/TNAs. The UV photoresponse of NNS/TNAs could be tuned by controlling the thickness of NNS. Abstract: A coupling heterostructure consisting of nickel oxide nanosheets (NNS) and titanium dioxide nanorod arrays (TNAs) was fabricated for self-powered solid-state ultraviolet (UV) photosensor applications. By controlling the thickness of the NNS layer by via varying the growth time from 1 to 5 h at a deposition temperature of 90 °C, the coupling NNS/TNAs heterojunction films were formed and their structural, optical, electrical and UV photoresponse properties were investigated. The photocurrent measured from the fabricated self-powered UV photosensor was improved by increasing the thickness of NNS from 140 to 170 nm under UV irradiation (365 nm, 750 µWcm −2 ) at 0 V bias. A maximum photocurrent density of 0.510 µA∙cm −2 was achieved for a sample with a NNS thickness of 170 nm and prepared with a 3 h NNS growth time. Our results showed that the fabricated NNS/TNAs heterojunction has potential applications for self-powered UV photosensors.